Robust measurement of vitamin A status in plasma and blood dried on paper. (December 2015) - Huang, Yichao; Clements, Peter Roy; Gibson, Robert Alan
Abstract: Vitamin A deficiency is the leading cause of preventable blindness in children and increases the risk of disease and death from severe infections. In addition, fat soluble vitamin A and associated retinoids directly regulate the expression of genes involved in fatty acid metabolism. Conventional methods for measuring vitamin A involve venipuncture, centrifugation and refrigeration all of which make measuring vitamin A in nutritional surveys expensive. We aimed to develop a simple and robust system for measurement of retinol (biomarker for vitamin A) using dried blood spot (DBS) samples. Low recoveries and inconsistent results reported by others were found to be due to poor extraction efficiency rather than retinol instability. Maintaining acid conditions during extraction resulted in recoveries >95% with <6.5% of coefficient of variation. Using isocratic high performance liquid chromatography, separation was achieved in <3.5 min. Detector response was linear ( R 2 =0.9939) within a range of 0.05–2 μg/mL, with a limit of quantification of 0.05 μg/mL. Retinol in DBS was shown to be stable (>95%) at room temperature for up to 10 weeks. DBS values for retinol were highly correlated with venous blood samples from 24 healthy subjects ( r =0.9724) and were consistent with results from a commercial laboratory. This simple and reliable method for the determination of vitamin A status should prove particularly valuable for population studies and large clinical trials. Highlights: Mild acidic conditions were found to be critical for retinol extractability from DBS. Retinol in DBS is stable for 10 weeks at room temperature in dark and dry conditions. Our DBS method is validated, robust and consistent with results from venous blood. The DBS method is a useful tool for population studies and large clinical trials.